Sustainable development of smart cities: A systematic review of the literature - Trindade, Evelin Priscila; Hinnig, Marcus Phoebe Farias; da Costa, Eduardo Moreira; Sabatini Marques, Jamile; Bastos, Rogério Cid; Yigitcanlar, Tan (Journal of open innovation, 2017)
This paper aims to analyse scientific studies focusing on both environmental sustainability and smart city concepts to understand the relationship between these two. In order to do so the study identifies information about researchers, models, frameworks and tools focused on the chosen themes. This research uses a qualitative methodology, through a systematic review of the literature, which examines the terms, ‘smart city’ and ‘sustainability’, aimed at sustainable development of smart cities. For this, three databases were used: Scopus, Science Direct, and Emerald Insight. This paper provides detailed information on the most recent scientific articles focusing on smart cities and sustainability issues. The paper can serve as a basis for researchers seeking background information for further investigations. The findings provide invaluable insights for scholars researching on the subject, and public managers considering applying those into practice in their cities.